PENGARUH ORGAN TATA KELOLA PERUSAHAAN TERHADAP MANAJEMEN LABA RIIL - Stella Florensia; Estralita Trisnawati; Oktavia Oktavia (Universitas Kristen Krida Wacana, 2020)
This study aims to determine the effect of the Corporate Governance organ by using the activities of the independent Corporate Governance organs (ie: financial expertise, gender, and political connections of the Corporate Governance organs) on real earnings management. Real earnings management is measured by abnormal measurements of each proxy using residuals, namely, Abnormal Cash Flow Operations, Abnormal Production Costs, and Abnormal Discretionary Expenses. The population in this study are publicly listed companies listed on the Stock Exchange, and the sample used was manufacturing companies listed on the Stock Exchange in the 2014-2018 period. Based on the purposive sampling method, 124 samples were obtained from manufacturing companies. The results showed that the activities of the Corporate Governance organs that have an influence on real earnings management are financial expertise. Furthermore, the activities of other Corporate Governance organs such as gender and political connections have no effect on real earnings management. Keywords: corporate governance, financial expertise, gender, political connections, real earnings management